Learning within the work process - often demanded, rarely supported!? - Kremer, Manfred [Verfasser] (My University, 2009)
Manfred Kremer, the President of the BIBB, regards the insight into practice in active and work-process-oriented teaching and learning concepts and curricula as the formula for success in a modern dual system of initial vocational training. The experience with dual-system vocational training gives German companies and education providers a head start. This is to be used more offensively in the European context. This also means supporting and continuously developing competence-oriented learning within the work process. (BIBB-Doku)
Keywords: L 2.1 Lernformen; Lernen am Arbeitsplatz; Erfahrungsorientiertes Lernen; Kompetenzentwicklung; Handlungskompetenz; Berufsausbildung